(untitled) (Research, Society and Development, 2020)
The present study aimed to know the quality of life of nursing professionals in Adult Intensive Care Units. This is an exploratory and descriptive research of a quantitative nature, which was carried out with nursing professionals working in Intensive Care Units in the Midwest region of the state of Rio Grande do Sul. Data collection was performed through instrument that measures quality of life, called Whoqol-bref. Among the results of this study, it is noteworthy that of the four domains evaluated, all obtained regular results, together with facets number one and two, which were evaluated separately. The importance of investigating the quality of life of the health professional, especially the nursing team, is due to the fact that it can contribute to minimizing risks inherent to the context of intensive care, reducing physical and mental health problems that may come to harm the individual’s lifestyle. It is concluded that nursing professionals, both nurses and nursing technicians who participated in the research, had a regular quality of life, a finding that corroborates with studies already found in the literature.